Strength Analysis of Welded Joints on the Frame Electric Bicycle - Kholis, Nur; Purwanto, Helmy; Mahendra, Isa (Suara Teknik : Jurnal Ilmiah, 2025)
This study aims to determine and analyze the electric bicycle frame on macro and micro structures, tensile testing, and hardness testing. This research uses hollow low carbon steel material with a length of 100 mm, width of 6 mm, and thickness of 2 mm. The method used is observation of macro and micro structures, vickers mickrohardness hardness testing. Furthermore, the specimens were welded with current variations of 100 A, 110 A, and 120 A with ASTM E8 design. From the observation of the macro structure, the best results are in the 110 A current variation compared to the 100 and 120 Ampere variations, because the 100 and 120 Ampere results experienced weld failure. The results of the microstructure test at a current of 100 A show that the pearlite phase dominates the parent metal and HAZ areas, while the welding area is dominated by Ferite. In testing the microstructure of 110 A current, it appears that pearlite dominates the parent metal and HAZ areas, while the welding area is dominated by martensite. In testing the microstructure of 120 A current can be seen in the parent metal and HAZ dominated by pearlite, while the welding area is dominated by martensite. From the Vicker microhardness test, the highest results in the welding area in the 120 A current variation and the lowest point in the parent metal in the 100 A current variation. The tensile test results show the highest value of yield stress 352.581 MPa and max stress 390.822 MPa shown in the 110 A current variation.